2011
DOI: 10.1371/journal.pone.0025241
|View full text |Cite
|
Sign up to set email alerts
|

Dicer1 Depletion in Male Germ Cells Leads to Infertility Due to Cumulative Meiotic and Spermiogenic Defects

Abstract: BackgroundSpermatogenesis is a complex biological process that requires a highly specialized control of gene expression. In the past decade, small non-coding RNAs have emerged as critical regulators of gene expression both at the transcriptional and post-transcriptional level. DICER1, an RNAse III endonuclease, is essential for the biogenesis of several classes of small RNAs, including microRNAs (miRNAs) and endogenous small interfering RNAs (endo-siRNAs), but is also critical for the degradation of toxic tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 54 publications
6
101
0
5
Order By: Relevance
“…Normozoospermic controls with normal P1/P2 ratio (10) • No significant quantitative differences between groups of patients with either an abnormally high or low P1/ P2 ratio compared to normal controls H19, MEST Normozoospermic controls (27) Oligozoospermic patients (96) • No aberration in MEST DNA methylation • Aberrant DNA methylation in H19 in oligozoospermic patients [62] cells and involved in proliferation, apoptosis, cell morphogenesis, and differentiation, abnormal expression of DDR1 in NOA patients may prevent primordial germ cell migration and development [48]. Table 1 gives a summary of the studies to date that analyze potential association of spermatozoal DNA methylation with male infertility.…”
Section: Alu and Line1mentioning
confidence: 99%
See 2 more Smart Citations
“…Normozoospermic controls with normal P1/P2 ratio (10) • No significant quantitative differences between groups of patients with either an abnormally high or low P1/ P2 ratio compared to normal controls H19, MEST Normozoospermic controls (27) Oligozoospermic patients (96) • No aberration in MEST DNA methylation • Aberrant DNA methylation in H19 in oligozoospermic patients [62] cells and involved in proliferation, apoptosis, cell morphogenesis, and differentiation, abnormal expression of DDR1 in NOA patients may prevent primordial germ cell migration and development [48]. Table 1 gives a summary of the studies to date that analyze potential association of spermatozoal DNA methylation with male infertility.…”
Section: Alu and Line1mentioning
confidence: 99%
“…miRNAs and endo-siRNAs are abundantly expressed in male germ cells throughout spermatogenesis, whereas piRNAs are only present in spermatocytes at the pachytene stage and in round spermatids [92,94]. The absolute requirement for miRNAs and endo-siRNAs for spermatogenesis has been shown by two initial studies where Dicer1 gene was knocked out in two different mouse models [95,96]. Germ-cell specific deletion of Dicer1 in these models has led to complete male infertility due to alterations in meiotic progression, increased spermatocyte apoptosis, and failure of haploid male germ cell differentiation.…”
Section: Role Of Protamination In Male Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Of relevance to the function of DICER1and DROSHA in miRNAs biogenesis and spermatogenesis, it has also been demonstrated that mutations or single nucleotide polymorphisms (SNP) in Dicer1 and Drosha is associated with male infertility. A mutation in Dicer1 or Drosha may cause global alterations of miRNA expression and result in the upregulation of their target genes, which in turn could affect other interacting factors such as the miRNA 17-92 cluster, leading to apoptosis of spermatozoa and abnormal semen quality [195]. In a study by Qin et al, [196], they reported a significant association between Dicer1 and Drosha SNP with abnormal semen parameters and idiopathic male infertility.…”
Section: Mirnas In Spermmentioning
confidence: 99%
“…Ces petits ARN, appelés piARN, s'associent avec les protéines PIWI pour former des complexes ribonucléoprotéiques impliqués notamment dans la répression des rétrotransposons au sein de la lignée germinale mâle. Concrètement, il existe deux souspopulations de piARN produites dans les cellules germinales mâles, [30,32] [25]. D'autres miARN tels que miR-322 et miR-323 ont été proposés comme favorisant la tumorigenèse des cellules germinales, se comportant donc comme des oncogènes potentiels [26].…”
Section: éTude Fonctionnelle Des Petits Arn Non Codants Lors De La Spunclassified